The Use Of Modern Innovative Technologies In The Management Of Sport Tourism Infrastructure (Eurasian Journal of Humanities and Social Sciences, 2026)
This article analyzes the role of modern innovative technologies in the management of sport tourism infrastructure. Sport tourism today requires not only stadiums, trails, hotels and transport systems, but also integrated digital platforms, smart monitoring tools, data-based decision-making and sustainable management models. The article examines how GIS, IoT, artificial intelligence, mobile applications, cloud platforms, digital marketing, virtual reality and smart ticketing systems improve the efficiency, safety and competitiveness of sport tourism destinations. Special attention is paid to infrastructure planning, visitor flow management, service quality, environmental sustainability and public-private cooperation. The study concludes that technological innovation should be understood not as an auxiliary tool, but as a strategic mechanism for developing sport tourism infrastructure.